Correlation between Endoscopic and Histopathological Findings in Gastric Lesions - Sharma, S.; Makaju, R.; Dhakal, R.; Purbey, B.; Gurung, R.B.; Shrestha, R. (Kathmandu University Medical Journal, 2017)
Background Stomach is a common site for wide variety of lesions. The visualisation of the site with biopsy leads to the early detection of the pathologic process and appropriate therapy. Objectives The objective of this study is to correlate the histopathological pattern of endoscopic biopsies with distribution of gastric lesions according to age and sex. Method The retrospective study was carried out among 50 cases with endoscopic biopsies and histopathological assessment, received at Department of Pathology, Dhulikhel Hospital- Kathmandu University Hospital. Result Out of 50 cases majority of cases were of male gender with male: female ratio was 1.3:1. Our study showed a poor correlation between endoscopic and histopathological evidence of inflammation in the stomach. Two cases were diagnosed as intestinal metaplasia which were diagnosed as ulcer and erosion endoscopically. Out of 32% of cases diagnosed endoscopically as ulcer, only one case was confirmed histopathologically. Our study showed good correlation in the cases of carcinoma. Out of 17 cases diagnosed endoscopically as gastric carcinoma correlated histopathologically as gastric adenocarcinoma. Majority of carcinoma cases showed ulcerating fungating growth followed by ulcero-proliferative growth. Conclusion Endoscopy is incomplete without biopsy and histopathology is the gold standard for the diagnosis of endoscopically detected lesions. Endoscopic examination and histopathological examination of suspected gastric lesions should go parallel and neither should be a substitute of each other.